Biscuit and the Baby - Capucilli, Alyssa Satin 1957-; Schories, Pat (New York : HarperCollins, 2005)
Biscuit, a young puppy, is eager to meet the new baby but must wait until nap time is over.
Keywords: Biscuit (Fictitious character) -- Fiction; Dogs -- Fiction; Babies -- Fiction